MdMYB1 Regulates Anthocyanin and Malate Accumulation by Directly Facilitating Their Transport into Vacuoles in Apples. Issue 3 (4th December 2015) - Hu, Da-Gang; Sun, Cui-Hui; Ma, Qi-Jun; You, Chun-Xiang; Cheng, Lailiang; Hao, Yu-Jin
Abstract : An MYB transcription factor influences organ coloration and acidity by activating the expression of the genes encoding vacuolar proton pump subunits as well as anthocyanin transporters and malate transporters. Abstract: Tonoplast transporters, including proton pumps and secondary transporters, are essential for plant cell function and for quality formation of fleshy fruits and ornamentals. Vacuolar transport of anthocyanins, malate, and other metabolites is directly or indirectly dependent on the H + -pumping activities of vacuolar H + -ATPase (VHA) and/or vacuolar H + -pyrophosphatase, but how these proton pumps are regulated in modulating vacuolar transport is largely unknown. Here, we report a transcription factor, MdMYB1, in apples that binds to the promoters of two genes encoding the B subunits of VHA, MdVHA-B1 and MdVHA-B2, to transcriptionally activate its expression, thereby enhancing VHA activity. A series of transgenic analyses in apples demonstrates that MdMYB1/10 controls cell pH and anthocyanin accumulation partially by regulating MdVHA-B1 and MdVHA-B2 . Furthermore, several other direct target genes of MdMYB10 are identified, including MdVHA-E2, MdVHP1, MdMATE-LIKE1, and MdtDT, which are involved in H + -pumping or in the transport of anthocyanins and malates into vacuoles. Finally, we show that the mechanism by which MYB controls malate and anthocyanin accumulation in apples also operates in Arabidopsis ( Arabidopsis thaliana ). These findings provide novel insights into how MYB transcription factors directly modulate the vacuolar transport system in addition to anthocyanin biosynthesis, consequently controlling organ coloration and cell pH in plants.